peran Peran Bimbingan Rohani Islam dalam Meningkatkan Spritualitas pada Remaja: Definition of Islamic Spiritual Guidance, Purpose or function of Spiritual Guidance Services, - adha, razita (Indonesian Journal of Islamic Counseling, 2025)
This study aims to analyze the role of Islamic spiritual guidance in improving spirituality in adolescents. The method used is literature review by examining various scientific sources such as journals, books, and relevant articles within the last ten years. The results of the study show that Islamic spiritual guidance plays a strategic role in shaping character, strengthening faith, and increasing the mental and moral resilience of adolescents. Through a holistic approach that includes worship guidance, spiritual assistance, and strengthening Islamic values, spiritual guidance can be a preventive, curative, and self-development solution for adolescents in facing the challenges of the times. Activities such as Islamic studies, religious counseling, and religious social activities have proven effective in instilling good habits, empathy, and building spiritual closeness to Allah SWT. Thus, Islamic spiritual guidance not only improves religious aspects, but also forms adolescents who are noble and beneficial to the surrounding environment.